2006
DOI: 10.1111/j.1467-9280.2006.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotion on Perception

Abstract: Recent studies have shown that emotionally significant stimuli are often better identified than neutral stimuli. It is not clear, however, whether these results are due to enhanced perceptual processing or to a bias favoring the identification of emotionally significant stimuli over neutral stimuli. The present study used a two-alternative forced-choice perceptual identification task to disentangle the effects of bias and enhanced processing. We found that emotionally significant targets were better identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 19 publications
14
84
1
1
Order By: Relevance
“…Supporting this possibility, several recent studies have found processing advantages for both positive and negative stimuli with pictorial (Brosch et al, 2008;Most et al, 2007) and word stimuli (Zeelenberg, Wagenmakers & Rotteveel, 2006) compared with neutral items. However, Experiment 1 could not assess this possibility because the enumeration of neutral valence faces was not measured.…”
Section: Experiments 5: Enumeration Without Distractors But With a Valmentioning
confidence: 66%
See 1 more Smart Citation
“…Supporting this possibility, several recent studies have found processing advantages for both positive and negative stimuli with pictorial (Brosch et al, 2008;Most et al, 2007) and word stimuli (Zeelenberg, Wagenmakers & Rotteveel, 2006) compared with neutral items. However, Experiment 1 could not assess this possibility because the enumeration of neutral valence faces was not measured.…”
Section: Experiments 5: Enumeration Without Distractors But With a Valmentioning
confidence: 66%
“…That is, the enumeration of negatively and positively valenced face stimuli was equivalent for both small and large numerosities. Third, it is possible that any behaviorallyrelevant emotional expression (whether positive or negative) might be used to guide attention efficiently (Brosch et al, 2008;Most et al, 2007;Zeelenberg, Wagenmakers & Rotteveel, 2006). According to this view, the efficiency of enumerating either positively or negatively affective faces should be equivalent, but both should be more efficient than the enumeration of neutral expression faces.…”
Section: Discussionmentioning
confidence: 99%
“…This can be a challenge when investigating recognition memory, since the number of available stimuli is relatively small and, * words regardless of whether the mode of presentation is visual (Zeelenberg et al, 2006) or auditory (Weger, Meier, Robinson, & Inhoff, 2007). In addition, when two stimuli are visually presented and one stimulus is emotionally valenced and the other is not, eye-tracking data indicate that the initial eye fixation is more likely to land on the emotionally valenced stimulus (Knight et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Paired t test comparisons Phelps (2004) reported greater accuracy for high-arousal words than for neutral words but did not measure differences in bias. However, the 2AFC procedure can be used to assess response bias by using null-choice comparisons (e.g., Glanzer & Adams, 1990;Glanzer, Adams, Iverson, & Kim, 1993;Hicks & Marsh, 1998;Malmberg & Murnane, 2002;Ratcliff & McKoon, 1995;Zeelenberg, Wagenmakers, & Rotteveel, 2006). For the null-choice trials, either two targets or two foils are presented that vary with respect to the factor that is manipulated experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…These findings about the role of attention in binding suggest that emotionally arousing stimuli might be more effectively bound with their features in initial perception, insofar as they elicit more intense focused attention (for a review see Mather, 2007). Previous studies have shown enhanced initial perceptual processing for emotional stimuli, as they are more likely than nonemotional stimuli to be correctly identified when shown very briefly (Zeelenberg, Wagenmakers, & Rotteveel, 2006) and less likely to be missed when presented in a rapid serial visual presentation with other stimuli (Anderson, 2005;Keil & Ihssen, 2004). Brain imaging studies reveal that when shown a series of pictures, people show more activation in visual processing regions for emotionally intense pictures than for emotionally neutral pictures (Bradley et al, 2003;Phan et al, 2002;Mather et al, 2006).…”
Section: Mechanisms Of Arousal-enhanced Bindingmentioning
confidence: 97%